Effects of Perfetti's Method on Cognition, Dexterity and Sensory Motor Function of the Upper Extremity in Stroke Patients: A Randomized Controlled Tria - Syed Muhammad Mateen; Ayesha Jamil; Umair Ahmad (Journal Riphah College of Rehabilitation Sciences, 2024)
Background: A stroke is the sudden loss of neural function caused by an interruption of blood flow to the brain. It causes symptoms such as paresis, hypoesthesia, cognitive impairment, spasticity.